Conditions for Presence of Personal Criminal Jurisdiction for Internal Security Forces Courts - Shaker, Kamel; Musbah, Sabah (Journal of Legal Sciences, 2022)
Reading Article First of Section 25 of Penal Trials Principles Law of Internal Forces Law makes us say that there are personal and objective regulations governing presence of jurisdiction of internal forces courts. It should be a source of law embodied by the personality of police as law in essence is a law of persons and the character of the perpetrator is not sufficient to determine jurisdiction of these courts. It should be linked with the subject condition, which completes the presence of jurisdiction for these courts, focusing on the essence of the crime and the interest to be protected by the criminal text with respect with the link between the crime and being a policeman. These conditions are closely tied. They do not operate separately but should be all present to achieve presence of jurisdiction.